Let $M$ be a Riemannian manifold. Assume $\gamma$ is a path in $M$ , such that it's image is a totally geodesic submanifold of $M$.

I am trying to prove (the seemingly trivial result) that $\gamma$ must be a reparametrization of a geodesic in $M$.

I came up with two possible explanations (described below). I would like to find a simpler argument.

First explanation:

Lemma(1): On a one dimensional Riemannian manifold, from any point there is only one path with constant speed $c$. (up to direction).


Since any one dimensional manifold $M$ is locally diffeomorphic to $\mathbb{R}$ and the question is local in nature, we can assume $M = (0,1)$ , with some arbitary metric.

Assume $\beta,\alpha:I \to M=(0,1) \, , \, \alpha(0)=\beta(0)=p, \dot\alpha(0)=\dot\beta(0) \, , \, \forall t \, \|\dot\alpha(t)\|=\|\dot\beta(t)\|=1$.

Since $\|\dot\alpha(t)\|=1$, $\dot\alpha(t) \in \{1,-1 \}$. By continuity it does not change sign. Since we assumed $\dot\alpha(0)=\dot\beta(0) \,$, it follows that $\forall t \, \dot\alpha(t)=\dot\beta(t)$, so now integration gives us $\alpha(t)=\beta(t)$.

Corollary(1): On a one dimensional Riemannian manifold, any path with constant speed is a geodesic.


Any geodesic has a constant speed, but from any point there is only one path with constant speed $c$. So this path must be a geodesic.

Proof of the claim:

Assume $S=\operatorname{Image} \gamma$ is a totally geodesic submanifold of $M$.

By corollary (1), if $\alpha$ is a constant speed reparametrization of $\gamma$, it's a geodesic in $S$. Hence it's a geodesic in $M$.

Second explanation:

Lemma(1): $S=\operatorname{Image} \gamma$ is totally geodesic iff (*) $\nabla_{\dot{\gamma}} \dot{\gamma} - \frac{g(\nabla_{\dot{\gamma}}\dot{\gamma}, \dot{\gamma} )}{g(\dot{\gamma}, \dot{\gamma})}\dot{\gamma} = 0.$

where $\nabla_{\dot{\gamma}} \dot{\gamma}$ is the usual covariant derivative (in M) along the path $\gamma$.


Since the question is local, we assume $\gamma$ is injective, hence it's a invertible from it's image. So any path $\alpha$ in $S$, is of the form: $\alpha(s)=\gamma(\phi(s))$.

So, $\dot \alpha(s)=\dot \gamma(\phi(s)) \cdot \phi'(s)$

$\nabla_{\dot{\alpha}}^M \dot{\alpha}=\phi''(s)\cdot \dot \gamma(\phi(s)) + \big(\phi'(s)\big)^2 \cdot \nabla_{\dot{\gamma}}^M \dot{\gamma} (\phi(s))$

The covariant derivative along a path in a Riemannian submanifold $S \subseteq M$ is the projection on $TS$ of the covariant derivative in $M$. In our case this just amounts to projecting on $sp\{\dot\gamma(t)\} \subseteq T_{\gamma(t)}M$:

$\nabla_{\dot{\alpha}}^S \dot{\alpha}=\phi''(s)\cdot \dot \gamma(\phi(s)) + \big(\phi'(s)\big)^2 \cdot Pr\nabla_{\dot{\gamma}}^M \dot{\gamma} (\phi(s))$

So it's easy to see that:

$\alpha$ is a geodesic in $S$ (i.e $\nabla_{\dot{\alpha}}^S \dot{\alpha}=0$) $\Rightarrow$ $\alpha$ is a geodesic in $M$ (i.e $\nabla_{\dot{\alpha}}^M \dot{\alpha}=0$) iff $\nabla_{\dot{\gamma}} \dot{\gamma} - \frac{g(\nabla_{\dot{\gamma}}\dot{\gamma}, \dot{\gamma} )}{g(\dot{\gamma}, \dot{\gamma})}\dot{\gamma} = 0.$

Proof of the claim:

Let $\alpha(s)=\gamma(\phi(s))$ be a constant speed reparametrization of $\gamma$, so $|\dot \alpha(s)|=|\dot \gamma(\phi(s))| \cdot |\phi'(s)|=1$.

This implies (assuming $\phi'(s) >0$) $\phi'(s) =\frac{1}{\|\dot \gamma(\phi(s)) \|}=\frac{1}{\sqrt{g(\dot \gamma,\dot \gamma) \circ \phi}}$


\begin{align} & \phi''(s)=-\frac{1}{\|\dot \gamma(\phi(s)) \|^2} \cdot \frac{1}{2\sqrt{g(\dot \gamma,\dot \gamma) \circ \phi}} \cdot \frac{d}{ds}\big( g(\dot \gamma,\dot \gamma) \circ \phi \big)= \\ & -\frac{1}{\|\dot \gamma(\phi(s)) \|^2} \cdot \frac{1}{2\sqrt{g(\dot \gamma,\dot \gamma) \circ \phi}} \cdot \Big( 2g(\nabla_{\dot{\gamma}} \dot{\gamma} ,\dot{\gamma}) \circ \phi \Big) \cdot \phi'(s) = \\ & - \big(\phi'(s)\big)^2 \cdot \frac{g(\nabla_{\dot{\gamma}}\dot{\gamma}, \dot{\gamma} )}{g(\dot{\gamma}, \dot{\gamma})} \circ \phi \end{align}

So finally,

$\nabla_{\dot{\alpha}} \dot{\alpha}=\phi''(s)\cdot \dot \gamma(\phi(s)) + \big(\phi'(s)\big)^2 \cdot \nabla_{\dot{\gamma}} \dot{\gamma} (\phi(s))= \big(\phi'(s)\big)^2 \cdot \Big( \big(\nabla_{\dot{\gamma}} \dot{\gamma} - \frac{g(\nabla_{\dot{\gamma}}\dot{\gamma}, \dot{\gamma} )}{g(\dot{\gamma}, \dot{\gamma})}\dot{\gamma} \big) \circ \phi \Big) =0$

As required.


In the spirit of your first argument, let $S \subseteq M$ be an embedded totally geodesic one-dimensional submanifold and choose $p \in S$. Let $\alpha \colon I \rightarrow S$ be a coordinate system around $p \in S$. In particular, $\alpha$ is an immersion and so we can compose $\alpha$ with a diffeomorphism and assume that $\alpha$ has constant speed. Then, computing in $S$ we have

$$ 0 = \frac{d}{dt} ||\dot{\alpha}(t)||^2 = 2 \left< \frac{D \dot{\alpha}}{dt}|_t, \dot{\alpha}(t) \right> $$

but since $S$ is one-dimensional and $\dot{\alpha}(t) \neq 0$, we must have $\frac{D\dot{\alpha}}{dt} \equiv 0$ showing that $\alpha$ is a geodesic in $S$ and thus in $M$.

  • $\begingroup$ Thanks. It seems you have answers to all my questions... $\endgroup$ – Asaf Shachar Nov 8 '15 at 10:20

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.